2007
DOI: 10.1097/01.tp.0000259617.21741.95
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Complications Associated With New-Onset Diabetes Mellitus in Renal Transplant Recipients

Abstract: NODM is associated with similar complications to those seen in the general population, but these appear to develop at an accelerated rate. Obesity and use of tacrolimus are the only modifiable factors that appear to affect risk of NODM or its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 35 publications
2
68
1
6
Order By: Relevance
“…It has been reported that Tacrolimus is more diabetogenic than CsA [30,31,32]. In the present work, no significant difference was found between the groups that received Tacrolimus and CsA.…”
Section: Discussioncontrasting
confidence: 40%
“…It has been reported that Tacrolimus is more diabetogenic than CsA [30,31,32]. In the present work, no significant difference was found between the groups that received Tacrolimus and CsA.…”
Section: Discussioncontrasting
confidence: 40%
“…It is difficult to estimate the actual rate of recurrence of diabetic nephropathy (DN) in renal allografts because about 20% of transplant patients may develop de novo onset of diabetes posttransplantation (PTDM), which can also eventually lead to de novo DN (85). Recurrence of DN accounted for only 1.8% of graft losses in one of the largest series of renal transplants in diabetic recipients (86).…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Incident PTDM within the first year after kidney transplantation doubles long-term mortality [3]. Diabetes-associated complications develop at a faster rate in PTDM than in non-transplant patients [4]. Comprehension of the risk factors and dynamics of PTDM is therefore crucial for developing preventive strategies in post-transplant patient care.…”
Section: Introductionmentioning
confidence: 99%